Expensive and cheap funds – Polish stock mutual fund fees in 2017 - Fraś, Alicja (Drogie i tanie fundusze – opłaty w polskich funduszach akcjiw 2017 roku, 2018)
Mutual fund fees are extraordinarily high in Poland – almost three times higher than in Western Europe and almost five times higher than in the United States. In fact is that from among 183 Polish open-ended stock mutual funds as many as 81 impose a management fee of 4%, which is the highest value in the sample. The question arises whether it is really worth to invest in funds from the more expensive group. Comparing funds charging the highest fees (4%) with the cheaper ones it seems that there is no statistically significant difference between rate of return, risk and efficiency. However, more expensive funds have on average higher costs, are three years older and have almost 70% bigger assets. This may suggest that a well-established market position – not performance – is the trigger for raising their fees. Interestingly, funds with a relatively high minimal initial contribution level (5,000 PLN) have significantly lower management fees with similar costs, total assets value and performance results. Further analysis has also indicated that the costs level (Total Expense Ratio) is higher for older funds, while it is not related to funds’ size
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 38-49
Keywords: mutual fund performance; performance; fees; charges